The Effects of Associative Priming on Retroactive Interference - Carroll, William W. (Tufts Archival Research Center, 2005)
We depend on our memory for events to inform the decisions we make in the moment. Whether you are trying to remember the name attached to a face you have only just meant, or trying to give crucial evidence to police about the events of a crime you witnessed, being able to remember the information is only part of it, this information needs to be accurate as well. Unfortunately, it has been consistently shown that newly learned material can cause people to forget events, or to provide inaccurate information when trying to recall an event in a phenomenon referred to as retroactive interference. This study seeks to shed light upon the mechanisms responsible for retroactive interference by associatively priming participants towards either the originally learned or newly learned information. A series of two experiments consistently showed that priming towards originally learned information prior to recall increased participants' recall accuracy. However, no effects were found when participants were primed towards newly learned', (interfering), information.